Fireproof door core fire-retardant filling material and preparation method thereof

CN121733669BActive Publication Date: 2026-10-27GUANGDONG HENGMEI PANEL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202512017988.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-30
Publication Date
2026-10-27
Estimated Expiration
2045-12-30

AI Technical Summary

Technical Problem

目前市面上的防火门芯填充材料主要包括珍珠岩板、岩棉板、酚醛树脂复合板材等传统类型,普遍存在阻燃抑烟协同性差、隔热效果有限、力学性能与稳定性不足、环保性欠佳等问题,难以满足现代建筑对防火门高安全性能、低环境影响的使用需求

Benefits of technology

本发明的防火门芯用阻燃填充材料以气凝胶隔热层和压缩防火层制成,以压缩防火层为支撑,木质纤维与岩棉经粉碎干燥形成复合骨料,经改性酚醛树脂粘结剂浸渍后,通过压缩与高温固化形成结构致密、抗压强度充足的中间层,其中改性酚醛树脂粘结剂经磷酸二氢铝与复合阻燃抑烟剂的协同改性,构建起磷-氮阻燃体系,复合阻燃抑烟剂以壳聚糖为基底,经三聚氰胺甲醛低聚体接枝氮系基团及钼酸铵配位钼酸根基团,钼酸根基团能够有效抑制烟雾与有毒气体生成。外层气凝胶隔热层采用正硅酸乙酯经水解缩合、凝胶化、疏水改性及超临界干燥制成,其高孔隙率的网络结构能高效阻断热传导与对流。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application relates to the technical field of flame-retardant materials, and discloses a flame-retardant filling material for a fireproof door core and a preparation method thereof, which comprises an outer layer and a middle layer; the outer layer is an aerogel heat insulation layer; and the middle layer is a compressed fireproof layer. The compressed fireproof layer is made of wood fibers and rock wool as raw materials, impregnated by a modified phenolic resin binder, gradiently compressed, and high-temperature cured; and the aerogel heat insulation layer is formed by coating aerogel slurry on both sides of the compressed fireproof layer and then pressure-curing. The flame-retardant filling material has the advantages of simple structure, excellent flame-retardant and fire-resistant performance, high compressive strength, reduced generation of harmful smoke in actual application, high safety factor, no need for special equipment in the preparation process, mild curing conditions, wide application in various fireproof doors, and suitability for industrialized production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of flame retardant materials technology, specifically to a flame retardant filler material for fireproof door cores and its preparation method. Background Technology

[0002] Fire doors, as core protective facilities in building fire safety systems, rely heavily on the performance of their core filling materials. These materials directly determine the fire door's flame-retardant and heat-insulating effects, structural stability, and environmental safety, playing a crucial role in ensuring the safe evacuation of personnel and the structural safety of buildings. With the continuous improvement of fire safety standards in modern buildings, the market demands higher comprehensive performance from fire door core filling materials. These materials must not only possess excellent flame retardancy and heat insulation but also consider mechanical strength, dimensional stability, and low-smoke, non-toxic environmental characteristics. Currently, the main fire door core filling materials on the market include traditional types such as perlite boards, rock wool boards, and phenolic resin composite boards. These materials generally suffer from poor synergy between flame retardancy and smoke suppression, limited heat insulation effects, insufficient mechanical properties and stability, and suboptimal environmental performance, making it difficult to meet the high safety performance and low environmental impact requirements of modern buildings. In summary, existing fire door core filling materials cannot simultaneously meet the comprehensive requirements of flame retardancy, heat insulation, mechanical properties, stability, and environmental protection, necessitating the development of a new filling material with more comprehensive performance. Summary of the Invention

[0003] (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides a flame-retardant filling material for fireproof door cores and its preparation method.

[0004] (II) Technical Solution To achieve the above objectives, the present invention provides the following technical solution: In a first aspect of the present invention, a flame-retardant filling material for fireproof door cores includes an outer layer and an intermediate layer, wherein the outer layer is an aerogel heat insulation layer and the intermediate layer is a compressed fireproof layer. The compressed fireproof layer is made of wood fiber and rock wool as raw materials, impregnated with modified phenolic resin binder, subjected to gradient compression and high temperature curing; The aerogel insulation layer is formed by coating both sides of the compressed fireproof layer with aerogel slurry and then curing it under pressure.

[0005] Furthermore, the preparation method of the modified phenolic resin adhesive includes the following steps: A1. Add 100-120 parts of deionized water to a beaker equipped with a stirrer, turn on the stirrer at 600-800 r / min, slowly add 10-15 parts of aluminum dihydrogen phosphate at room temperature, stir for 10-15 min to obtain an aqueous solution of aluminum dihydrogen phosphate. A2. Add 40-50 parts of phenolic resin and 300-500 parts of anhydrous ethanol to the reaction vessel, heat to 50-60℃, stir at 600-800 r / min for 10-15 min, add 4-6 parts of hexamethylenetetramine, stir for 10-15 min, and obtain the phenolic resin matrix. A3. Slowly drip an aqueous solution of aluminum dihydrogen phosphate into the phenolic resin matrix, then add 4-8 parts of composite flame retardant and smoke suppressant, adjust the stirring speed to 800-1000 r / min, keep it at 60-80℃ for 10-30 min, after the holding time is completed, transfer it to a vacuum distillation apparatus, with a vacuum degree of 0.06-0.08 MPa, and heat it to 40-50℃. The solid content reaches 40-50%, and the modified phenolic resin binder is obtained.

[0006] Furthermore, the preparation method of the composite flame retardant and smoke suppressant includes the following steps: B1. Add 10-15 parts of chitosan to 200-400 parts of glacial acetic acid solution with a mass fraction of 8-16%, start stirring at 600-800 r / min, and stir until dissolved to obtain a chitosan solution; add 8-12 parts of formaldehyde aqueous solution with a mass fraction of 30-38% and 90-110 parts of deionized water to a reaction vessel equipped with a stirrer, start stirring at 300-500 r / min, add ammonia dropwise at room temperature to adjust the pH to 8.0-8.5, add 15-20 parts of melamine and 1-2 parts of ethylene glycol, heat to 60-65℃, keep warm and stir for 30-40 min to form a melamine-formaldehyde oligomer solution, and cool to 30-40℃ for later use; B2. Slowly add the melamine-formaldehyde oligomer solution to the chitosan solution, increase the stirring speed to 700~900 r / min, keep it at 40~50℃ and stir for 1~1.5 h to obtain the modified chitosan dispersion. B3. With the modified chitosan dispersion at a temperature of 50-60℃ and a stirring speed of 600-800 r / min, slowly add 10-15 parts of ammonium molybdate, raise the temperature to 50-60℃, keep stirring at this temperature for 40-60 min, cool naturally to room temperature, dry in an oven at 60-80℃ for 8-10 h, pulverize in a high-speed pulverizer, and pass through a 100-200 mesh sieve to obtain a composite flame retardant and smoke suppressant.

[0007] Furthermore, the method for preparing the compression fireproof layer includes the following steps: C1. Place 30-40 parts of wood fiber and 25-35 parts of rock wool in an oven at 60-80℃ and dry for 2-3 hours. After cooling to room temperature, place them in a hammer mill and crush them to a particle size of less than 25 mm to obtain composite aggregate for later use. C2. Take out 25-35 parts of modified phenolic resin binder, add 200-400 parts of deionized water, stir for 10-15 min, add 3-5 parts of light calcium carbonate, stir at 1000-1200 r / min for 10-15 min, and obtain the binder system. C3. Add composite aggregate to the mixer, start stirring at 300~400 r / min for 5~10 min, remove and immerse in the binder system, stir at 600~800 r / min for 20~30 min, and after impregnation, remove to obtain the mixture; C4. Pour the mixture evenly into the mold, with a thickness 30-50% thicker than the final product. Smooth the surface with a scraper, apply pressure, and then place the mold containing the mixture into a constant temperature oven. Heat to 120-130℃ and keep at that temperature for 2-2.5 hours. Then heat to 150-160℃ and keep at that temperature for 0.5-1 hour. After curing, allow it to cool naturally to room temperature. Open the mold, remove the cured blank, and you will get the compressed fireproof layer.

[0008] Furthermore, in step C4, the pressure is applied at 5-8 MPa for 3-5 minutes, then increased to 12-15 MPa and held for 5-10 minutes.

[0009] A second aspect of the present invention provides a method for preparing a flame-retardant filling material for fireproof door cores, characterized by comprising the following steps: S1. Mix 100-150 parts of tetraethyl orthosilicate with 150-200 parts of anhydrous ethanol until homogeneous, add 200-300 parts of deionized water, add hydrochloric acid dropwise to adjust the pH to 2-3, stir at 50-60℃ for 1-1.5 h to form silica sol. S2. Add ammonia to the silica sol to adjust the pH to 8-9, let it stand at room temperature for 12-24 h to form a wet gel, immerse it in a mixture of 8-12 parts of trimethylchlorosilane and 50-80 parts of anhydrous ethanol, keep it at 60-80℃ for 2-3 h, dry it in a supercritical drying device to obtain aerogel powder, add 50-80 parts of anhydrous ethanol, stir for 10-30 min to obtain aerogel slurry; S3. Apply the aerogel slurry evenly to both sides of the compressed fireproof layer, let it stand at room temperature for 10~30 min, place it in a mold after coating, apply pressure of 3~5 MPa, heat to 120~130℃, keep it at that temperature for 2~3 h, let it cool naturally to room temperature, and trim the edge burrs to obtain the flame-retardant filler material.

[0010] Furthermore, in step S2, the supercritical drying equipment uses CO2 as the medium and dries the material at 30~35℃ and 7~7.5 MPa for 4~6 h.

[0011] Further, in step S3, the aerogel slurry coating method is to place the compressed fireproof layer horizontally on the coating workbench, turn on the scraper coating machine, and uniformly scrape the aerogel slurry onto the first side of the compressed fireproof layer with a thickness of 3~5 mm. After standing for 8~15 minutes, the compressed fireproof layer is flipped over, and the scraping steps are repeated to complete the coating of the second side of the aerogel slurry.

[0012] (iii) Beneficial technical effects The fire-retardant filling material for the fireproof door core of this invention is made of an aerogel insulation layer and a compressed fireproof layer. The compressed fireproof layer serves as a support. Wood fibers and rock wool are pulverized and dried to form a composite aggregate, which is then impregnated with a modified phenolic resin binder. After compression and high-temperature curing, a dense intermediate layer with sufficient compressive strength is formed. The modified phenolic resin binder is synergistically modified with aluminum dihydrogen phosphate and a composite flame-retardant and smoke-suppressing agent to construct a phosphorus-nitrogen flame-retardant system. The composite flame-retardant and smoke-suppressing agent is based on chitosan and grafted with nitrogen groups and ammonium molybdate-coordinated molybdate groups using melamine-formaldehyde oligomers. The molybdate groups effectively inhibit the generation of smoke and toxic gases. The outer aerogel insulation layer is made of tetraethyl orthosilicate through hydrolysis condensation, gelation, hydrophobic modification, and supercritical drying. Its high-porosity network structure efficiently blocks heat conduction and convection.

[0013] The flame-retardant filler material of this invention has a simple structure, provides excellent flame-retardant and fire-resistant properties, has high mechanical properties, can reduce the generation of harmful fumes in practical applications, has a high safety factor, requires no special equipment in the preparation process, has mild curing conditions, is widely used in various fire doors, and is suitable for industrial production. Detailed Implementation

[0014] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0015] Unless otherwise specified, all components of the flame-retardant filler material formulation of this invention are commercially available. All parts used in this invention are parts by weight; The wood fiber is pine fiber, purchased from Shandong Sentai Wood Industry Co., Ltd. Rock wool fibers with a diameter of 3~7 μm were purchased from Hebei Huamei Energy-Saving Technology Group Co., Ltd. The phenolic resin was of the resole type and was purchased from Sinopec Baling Petrochemical Co., Ltd. Light calcium carbonate with a particle size ≤2 μm was purchased from Zhejiang Chuanhua Huayang Chemical Co., Ltd. Example 1 A flame-retardant filling material for fireproof door cores includes an outer layer and an inner layer, wherein the outer layer is an aerogel heat insulation layer and the inner layer is a compressed fireproof layer; The compressed fireproof layer is made of wood fiber and rock wool as raw materials, impregnated with modified phenolic resin binder, gradient compressed and cured at high temperature; The aerogel insulation layer is formed by coating both sides of the compressed fireproof layer with aerogel slurry and then curing it under pressure.

[0016] The preparation method of modified phenolic resin adhesive includes the following steps: A1. Add 100 parts of deionized water to a beaker equipped with a stirrer, turn on the stirrer at 600 r / min, slowly add 10 parts of aluminum dihydrogen phosphate at room temperature, stir for 10 min to obtain an aqueous solution of aluminum dihydrogen phosphate. A2. Add 40 parts of phenolic resin and 300 parts of anhydrous ethanol to the reaction vessel, heat to 50°C, stir at 600 r / min for 10 min, add 4 parts of hexamethylenetetramine and stir for 10 min to obtain the phenolic resin matrix. A3. Slowly drip an aqueous solution of aluminum dihydrogen phosphate into the phenolic resin matrix, then add 4 parts of composite flame retardant and smoke suppressant, adjust the stirring speed to 800 r / min, keep it at 60℃ for 10 min, after the heat preservation is completed, transfer it to a vacuum distillation apparatus, vacuum degree 0.06MPa, heat to 40℃, the solid content reaches 40%, and the modified phenolic resin binder is obtained.

[0017] The preparation method of the composite flame retardant and smoke suppressant includes the following steps: B1. Add 10 parts of chitosan to 200 parts of 8% glacial acetic acid solution, start stirring at 600 r / min until dissolved to obtain chitosan solution; add 8 parts of 30% formaldehyde aqueous solution and 90 parts of deionized water to a reaction vessel equipped with a stirrer, start stirring at 300 r / min, add ammonia dropwise at room temperature to adjust pH to 8.0, add 15 parts of melamine and 1 part of ethylene glycol, heat to 60℃, keep warm and stir for 30 min to form melamine-formaldehyde oligomer solution, cool to 30℃ for later use; B2. Slowly add the melamine-formaldehyde oligomer solution to the chitosan solution, increase the stirring speed to 700 r / min, keep it at 40℃ and stir for 1 h to obtain the modified chitosan dispersion. B3. The modified chitosan dispersion was heated to 50℃ and stirred at 600 r / min. 10 parts of ammonium molybdate were slowly added, the temperature was raised to 50℃, and the mixture was stirred for 40 min. It was then naturally cooled to room temperature and dried in a 60℃ oven for 8 h. The mixture was then pulverized in a high-speed pulverizer and passed through a 100-mesh sieve to obtain a composite flame retardant and smoke suppressant.

[0018] The method for preparing a compression fireproof layer includes the following steps: C1. Place 30 parts of wood fiber and 25 parts of rock wool in a 60℃ oven and dry for 2 hours. After cooling to room temperature, place them in a hammer mill and crush them to a particle size of less than 25 mm to obtain composite aggregate for later use. C2. Take out 25 parts of modified phenolic resin binder, add 200 parts of deionized water, stir for 10 min, add 3 parts of light calcium carbonate, stir at 1000 r / min for 10 min, and obtain the binder system. C3. Add composite aggregate to the mixer, start stirring at 300 r / min for 5 min, remove and immerse in the binder system, stir at 600 r / min for 20 min, and after impregnation, remove to obtain the mixture; C4. Pour the mixture evenly into the mold, with a thickness 30% thicker than the final product. Smooth the surface with a scraper, apply pressure, and then send the mold containing the mixture into a constant temperature oven. Heat to 120°C and keep warm for 2 hours. Heat to 150°C and keep warm for 0.5 hours. After curing, allow it to cool naturally to room temperature. Open the mold, remove the cured blank, and obtain the compressed fireproof layer.

[0019] In step C4, the pressure is applied at 5 MPa for 3 minutes, then increased to 12 MPa and held for 5 minutes.

[0020] A method for preparing a flame-retardant filling material for fireproof door cores includes the following steps: S1. Mix 100 parts of tetraethyl orthosilicate and 150 parts of anhydrous ethanol evenly, add 200 parts of deionized water, add hydrochloric acid dropwise to adjust the pH to 2, stir at 50℃ for 1 h to form silica sol. S2. Add ammonia to the silica sol to adjust the pH to 8, let it stand at room temperature for 12 h to form a wet gel, immerse it in a mixture of 8 parts trimethylchlorosilane and 50 parts anhydrous ethanol, keep it at 60℃ for 2 h, put it into a supercritical drying device to dry it and obtain aerogel powder. Add 50 parts anhydrous ethanol and stir for 10 min to obtain aerogel slurry. S3. Apply the aerogel slurry evenly to both sides of the compressed fireproof layer, let it stand at room temperature for 10 minutes, place it in a mold after coating, apply a pressure of 3 MPa, heat it to 120℃, keep it at that temperature for 2 hours, let it cool naturally to room temperature, and trim the edge burrs to obtain the flame-retardant filler material.

[0021] In step S2, the supercritical drying equipment uses CO2 as the medium and dries the product at 30°C and 7 MPa for 4 hours.

[0022] In step S3, the aerogel slurry coating method is as follows: place the compressed fireproof layer horizontally on the coating workbench, turn on the scraper coating machine, and evenly scrape the aerogel slurry onto the first side of the compressed fireproof layer with a thickness of 3 mm. Let it stand for 8 minutes, then turn the compressed fireproof layer over and repeat the scraping steps to complete the coating of the second side of the aerogel slurry.

[0023] Example 2 A flame-retardant filling material for fireproof door cores includes an outer layer and an inner layer, wherein the outer layer is an aerogel heat insulation layer and the inner layer is a compressed fireproof layer; The compressed fireproof layer is made of wood fiber and rock wool as raw materials, impregnated with modified phenolic resin binder, gradient compressed and cured at high temperature; The aerogel insulation layer is formed by coating both sides of the compressed fireproof layer with aerogel slurry and then curing it under pressure.

[0024] The preparation method of modified phenolic resin adhesive includes the following steps: A1. Add 110 parts of deionized water to a beaker equipped with a stirrer, turn on the stirrer at 700 r / min, slowly add 12 parts of aluminum dihydrogen phosphate at room temperature, stir for 10 min, and obtain an aqueous solution of aluminum dihydrogen phosphate. A2. Add 45 parts of phenolic resin and 400 parts of anhydrous ethanol to the reaction vessel, heat to 55°C, stir at 700 r / min for 10 min, add 5 parts of hexamethylenetetramine and stir for 15 min to obtain the phenolic resin matrix. A3. Slowly drip an aqueous solution of aluminum dihydrogen phosphate into the phenolic resin matrix, then add 6 parts of composite flame retardant and smoke suppressant, adjust the stirring speed to 900 r / min, keep it at 70℃ for 20 min, after the heat preservation is completed, transfer it to a vacuum distillation apparatus, vacuum degree 0.07MPa, heat to 45℃, the solid content reaches 45%, and the modified phenolic resin binder is obtained.

[0025] The preparation method of the composite flame retardant and smoke suppressant includes the following steps: B1. Add 12 parts of chitosan to 300 parts of 12% glacial acetic acid solution, start stirring at 700 r / min until dissolved to obtain chitosan solution; add 10 parts of 35% formaldehyde aqueous solution and 100 parts of deionized water to a reaction vessel equipped with a stirrer, start stirring at 400 r / min, add ammonia dropwise at room temperature to adjust pH to 8.2, add 18 parts of melamine and 1.5 parts of ethylene glycol, heat to 62℃, keep warm and stir for 35 min to form melamine-formaldehyde oligomer solution, cool to 35℃ for later use; B2. Slowly add the melamine-formaldehyde oligomer solution to the chitosan solution, increase the stirring speed to 800 r / min, keep it at 45℃ and stir for 1 h to obtain the modified chitosan dispersion. B3. The modified chitosan dispersion was heated to 55℃ and stirred at 700 r / min. 12 parts of ammonium molybdate were slowly added, the temperature was raised to 55℃, and the mixture was stirred for 50 min. It was then naturally cooled to room temperature and dried in a 70℃ oven for 9 h. The mixture was then pulverized in a high-speed pulverizer and passed through a 150-mesh sieve to obtain a composite flame retardant and smoke suppressant.

[0026] The method for preparing a compression fireproof layer includes the following steps: C1. Place 35 parts of wood fiber and 30 parts of rock wool in a 70℃ oven and dry for 2.5 h. Cool to room temperature, place in a hammer mill and crush to a particle size of less than 25 mm to obtain composite aggregate for later use. C2. Take out 30 parts of modified phenolic resin adhesive, add 300 parts of deionized water, stir for 12 min, add 4 parts of light calcium carbonate, stir at 1100 r / min for 10 min, and obtain the adhesive system. C3. Add composite aggregate to the mixer, start stirring at 350 r / min for 5 min, remove and immerse in the binder system, stir at 700 r / min for 25 min, and after impregnation, remove to obtain the mixture; C4. Pour the mixture evenly into the mold, with a thickness 40% thicker than the final product. Smooth the surface with a scraper, apply pressure, and then send the mold containing the mixture into a constant temperature oven. Heat to 125℃ and keep warm for 2 hours. Heat to 155℃ and keep warm for 0.5 hours. After curing, allow it to cool naturally to room temperature. Open the mold, remove the cured blank, and obtain the compressed fireproof layer.

[0027] In step C4, the pressure is applied at 6 MPa for 4 minutes, then increased to 13 MPa and held for 5 minutes.

[0028] A method for preparing a flame-retardant filling material for fireproof door cores includes the following steps: S1. Mix 120 parts of tetraethyl orthosilicate and 180 parts of anhydrous ethanol evenly, add 250 parts of deionized water, add hydrochloric acid dropwise to adjust the pH to 2.5, stir at 50℃ for 1 h to form silica sol. S2. Add ammonia to the silica sol to adjust the pH to 8.5, let it stand at room temperature for 15 h to form a wet gel, immerse it in a mixture of 10 parts trimethylchlorosilane and 60 parts anhydrous ethanol, keep it at 70℃ for 2.5 h, put it into a supercritical drying device to dry it to obtain aerogel powder, add 60 parts anhydrous ethanol, stir for 20 min to obtain aerogel slurry. S3. Apply the aerogel slurry evenly to both sides of the compressed fireproof layer, let it stand at room temperature for 20 minutes, place it in a mold after coating, apply a pressure of 4 MPa, heat it to 125℃, keep it at that temperature for 2.5 h, let it cool naturally to room temperature, and trim the edge burrs to obtain the flame-retardant filler material.

[0029] In step S2, the supercritical drying equipment uses CO2 as the medium and dries the product at 32°C and 7.2 MPa for 5 hours.

[0030] In step S3, the aerogel slurry coating method is as follows: place the compressed fireproof layer horizontally on the coating workbench, turn on the scraper coating machine, and evenly scrape the aerogel slurry onto the first side of the compressed fireproof layer with a thickness of 4 mm. Let it stand for 10 minutes, turn the compressed fireproof layer over, and repeat the scraping steps to complete the coating of the second side of the aerogel slurry.

[0031] Example 3 A flame-retardant filling material for fireproof door cores includes an outer layer and an inner layer, wherein the outer layer is an aerogel heat insulation layer and the inner layer is a compressed fireproof layer; The compressed fireproof layer is made of wood fiber and rock wool as raw materials, impregnated with modified phenolic resin binder, gradient compressed and cured at high temperature; The aerogel insulation layer is formed by coating both sides of the compressed fireproof layer with aerogel slurry and then curing it under pressure.

[0032] The preparation method of modified phenolic resin adhesive includes the following steps: A1. Add 120 parts of deionized water to a beaker equipped with a stirrer, turn on the stirrer at 800 r / min, slowly add 15 parts of aluminum dihydrogen phosphate at room temperature, stir for 15 min, and obtain an aqueous solution of aluminum dihydrogen phosphate. A2. Add 50 parts of phenolic resin and 500 parts of anhydrous ethanol to the reaction vessel, heat to 60°C, stir at 800 r / min for 15 min, add 6 parts of hexamethylenetetramine, and stir for 15 min to obtain the phenolic resin matrix. A3. Slowly drip an aqueous solution of aluminum dihydrogen phosphate into the phenolic resin matrix, then add 8 parts of composite flame retardant and smoke suppressant, adjust the stirring speed to 1000 r / min, keep it at 80℃ for 30 min, after the heat preservation is completed, transfer it to a vacuum distillation apparatus, vacuum degree 0.08 MPa, heat to 50℃, the solid content reaches 50%, and the modified phenolic resin binder is obtained.

[0033] The preparation method of the composite flame retardant and smoke suppressant includes the following steps: B1. Add 15 parts of chitosan to 400 parts of 16% glacial acetic acid solution, start stirring at 800 r / min, and stir until dissolved to obtain chitosan solution; add 12 parts of 38% formaldehyde aqueous solution and 110 parts of deionized water to a reaction vessel equipped with a stirrer, start stirring at 500 r / min, add ammonia dropwise at room temperature to adjust pH to 8.5, add 20 parts of melamine and 2 parts of ethylene glycol, heat to 65℃, keep warm and stir for 40 min to form melamine-formaldehyde oligomer solution, and cool to 40℃ for later use; B2. Slowly add the melamine-formaldehyde oligomer solution to the chitosan solution, increase the stirring speed to 900 r / min, and keep stirring at 50℃ for 1.5 h to obtain the modified chitosan dispersion. B3. The modified chitosan dispersion was heated to 60℃ and stirred at 800 r / min. 15 parts of ammonium molybdate were slowly added, the temperature was raised to 60℃, and the mixture was stirred for 60 min. It was then naturally cooled to room temperature and dried in an 80℃ oven for 10 h. The mixture was then pulverized in a high-speed pulverizer and passed through a 200-mesh sieve to obtain a composite flame retardant and smoke suppressant.

[0034] The method for preparing a compression fireproof layer includes the following steps: C1. Place 40 parts of wood fiber and 35 parts of rock wool in an 80℃ oven and dry for 3 hours. After cooling to room temperature, place them in a hammer mill and crush them to a particle size of less than 25 mm to obtain composite aggregate for later use. C2. Take out 35 parts of modified phenolic resin adhesive, add 400 parts of deionized water, stir for 15 min, add 5 parts of light calcium carbonate, stir at 1200 r / min for 15 min, and obtain the adhesive system. C3. Add composite aggregate to the mixer, start stirring at 400 r / min for 10 min, remove and immerse in the binder system, stir at 800 r / min for 30 min, and after impregnation, remove to obtain the mixture; C4. Pour the mixture evenly into the mold, with a thickness 50% greater than the final product. Smooth the surface with a scraper, apply pressure, and then send the mold containing the mixture into a constant temperature oven. Heat to 130°C and keep at that temperature for 2.5 hours. Then heat to 160°C and keep at that temperature for 1 hour. After curing, allow it to cool naturally to room temperature. Open the mold, remove the cured blank, and you will get the compressed fireproof layer.

[0035] In step C4, the pressure is applied at 8 MPa for 5 minutes, then increased to 15 MPa and held for 10 minutes.

[0036] A method for preparing a flame-retardant filling material for fireproof door cores includes the following steps: S1. Mix 150 parts of tetraethyl orthosilicate and 200 parts of anhydrous ethanol evenly, add 300 parts of deionized water, add hydrochloric acid dropwise to adjust the pH to 3, stir at 60℃ for 1.5 h to form silica sol. S2. Add ammonia to the silica sol to adjust the pH to 9, let it stand at room temperature for 24 h to form a wet gel, immerse it in a mixture of 12 parts trimethylchlorosilane and 80 parts anhydrous ethanol, keep it at 80℃ for 3 h, put it into a supercritical drying device to dry it to obtain aerogel powder, add 80 parts anhydrous ethanol, stir for 30 min to obtain aerogel slurry. S3. Apply the aerogel slurry evenly to both sides of the compressed fireproof layer, let it stand at room temperature for 30 minutes, place it in a mold after coating, apply a pressure of 5 MPa, heat it to 130℃, keep it at that temperature for 3 hours, let it cool naturally to room temperature, and trim the edge burrs to obtain the flame-retardant filler material.

[0037] In step S2, the supercritical drying equipment uses CO2 as the medium and dries the product at 35°C and 7.5 MPa for 6 hours.

[0038] In step S3, the aerogel slurry coating method is as follows: place the compressed fireproof layer horizontally on the coating workbench, turn on the scraper coating machine, and evenly scrape the aerogel slurry onto the first side of the compressed fireproof layer with a thickness of 5 mm. Let it stand for 15 minutes, turn the compressed fireproof layer over, and repeat the scraping steps to complete the coating of the second side of the aerogel slurry.

[0039] Comparative Example 1: The composite flame retardant and smoke suppressant was missing in step A3, while the other components and processes were the same as in Example 1.

[0040] Comparative Example 2: The aerogel insulation layer was replaced with a silica coating, and the remaining components and processes were the same as in Example 1; Preparation method of silica coating: Mix 100 parts of tetraethyl orthosilicate with 50 parts of anhydrous ethanol, add 10 parts of deionized water and 2 parts of hydrochloric acid (pH=2), stir for 30 min to form silica sol, directly coat it on both sides of the compressed fireproof layer (thickness 3mm), cure at room temperature for 24 h, and then keep it at 120℃ for 2 h.

[0041] Comparative Example 3: The modified phenolic resin binder was replaced with an equal mass of phenolic resin binder with a solid content of 40%, the solvent was ethanol, and the remaining components and processes were the same as in Example 1.

[0042] Performance testing: 1. Compression fireproof layer test: Combustion performance (combustion rating, oxygen index): Refer to standard GB 8624-2012; Fire resistance rating: Refer to standard GB 12955-2008; Smoke density rating: Refer to standard GB / T 8627-2007; 2. Aerogel insulation layer test: Thermal conductivity (25℃): Refer to standard GB / T 10294-2008; 3. Flame-retardant filler material test: Compressive strength: Refer to standard GB / T 5486-2008; Table 1 Table 2 As shown in the table above, Examples 1-3 all have a Class A non-combustible flammability rating, an oxygen index of 38.5-41.8%, a fire resistance limit of 1.7-2.0 h, and a smoke density rating of 22-26. Comparative Example 1 has a Class B1 flame-retardant flammability rating, an oxygen index of 28.3%, a fire resistance limit of 1.2 h, and a smoke density rating of 58. Comparative Example 3 has a Class B2 combustible flammability rating, an oxygen index of 24.5%, a fire resistance limit of 0.8 h, and a smoke density rating of 65. This indicates that the composite flame retardant and smoke suppressant, along with aluminum dihydrogen phosphate, can effectively improve the flame retardancy of the material and reduce smoke generation. The thermal conductivity of Examples 1-3 is 0.028-0.032 W / (m·K), and the thermal conductivity of Comparative Example 2 is 0.115 W / (m·K), indicating that the aerogel insulation layer can effectively insulate heat and improve the fire resistance of the flame-retardant material.

[0043] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A flame-retardant filling material for fireproof door cores, characterized in that, It consists of an outer layer and an inner layer. The outer layer is an aerogel insulation layer, and the inner layer is a compressed fireproof layer. The compressed fireproof layer is made of wood fiber and rock wool as raw materials, impregnated with modified phenolic resin binder, gradient compressed and cured at high temperature; The aerogel insulation layer is formed by coating aerogel slurry onto both sides of a compressed fireproof layer and then curing it under pressure. The preparation method of modified phenolic resin adhesive includes the following steps: A1. Add 100-120 parts of deionized water to a beaker equipped with a stirrer, turn on the stirrer at 600-800 r / min, slowly add 10-15 parts of aluminum dihydrogen phosphate at room temperature, stir for 10-15 min to obtain an aqueous solution of aluminum dihydrogen phosphate. A2. Add 40-50 parts of phenolic resin and 300-500 parts of anhydrous ethanol to the reaction vessel, heat to 50-60℃, stir at 600-800 r / min for 10-15 min, add 4-6 parts of hexamethylenetetramine, stir for 10-15 min, and obtain the phenolic resin matrix. A3. Slowly drip an aqueous solution of aluminum dihydrogen phosphate into the phenolic resin matrix, then add 4-8 parts of composite flame retardant and smoke suppressant, adjust the stirring speed to 800-1000 r / min, keep it at 60-80℃ for 10-30 min, after the holding time is completed, transfer it to a vacuum distillation apparatus, vacuum degree 0.06-0.08 MPa, heat to 40-50℃, the solid content reaches 40-50%, and the modified phenolic resin binder is obtained. The preparation method of the composite flame retardant and smoke suppressant includes the following steps: B1. Add 10-15 parts of chitosan to 200-400 parts of 8-16% glacial acetic acid solution, start stirring at 600-800 r / min until dissolved to obtain chitosan solution; add 8-12 parts of 30-38% formaldehyde aqueous solution and 90-110 parts of deionized water to a reactor equipped with a stirrer, start stirring at 300-500 r / min, add ammonia dropwise at room temperature to adjust pH to 8.0-8.5, add 15-20 parts of melamine and 1-2 parts of ethylene glycol, heat to 60-65℃, keep warm and stir for 30-40 min to form melamine-formaldehyde oligomer solution, cool to 30-40℃ for later use; B2. Slowly add the melamine-formaldehyde oligomer solution to the chitosan solution, increase the stirring speed to 700~900 r / min, keep it at 40~50℃ and stir for 1~1.5 h to obtain the modified chitosan dispersion. B3. The modified chitosan dispersion is heated to 50-60℃ and stirred at 600-800 r / min. 10-15 parts of ammonium molybdate are slowly added, the temperature is raised to 50-60℃, and the mixture is stirred for 40-60 min. It is then naturally cooled to room temperature and dried in an oven at 60-80℃ for 8-10 h. The mixture is then pulverized in a high-speed pulverizer and passed through a 100-200 mesh sieve to obtain a composite flame retardant and smoke suppressant. The method for preparing a compression fireproof layer includes the following steps: C1. Place 30-40 parts of wood fiber and 25-35 parts of rock wool in an oven at 60-80℃ and dry for 2-3 hours. After cooling to room temperature, place them in a hammer mill and crush them to a particle size of less than 25 mm to obtain composite aggregate for later use. C2. Take out 25-35 parts of modified phenolic resin binder, add 200-400 parts of deionized water, stir for 10-15 min, add 3-5 parts of light calcium carbonate, stir at 1000-1200 r / min for 10-15 min, and obtain the binder system. C3. Add composite aggregate to the mixer, start stirring at 300~400 r / min for 5~10 min, remove and immerse in the binder system, stir at 600~800 r / min for 20~30 min, and after impregnation, remove to obtain the mixture; C4. Pour the mixture evenly into the mold, with a thickness 30-50% thicker than the final product. Smooth the surface with a scraper, apply pressure, and then place the mold containing the mixture into a constant temperature oven. Heat to 120-130℃ and keep at that temperature for 2-2.5 hours. Then heat to 150-160℃ and keep at that temperature for 0.5-1 hour. After curing, allow it to cool naturally to room temperature. Open the mold, remove the cured blank, and you will get the compressed fireproof layer.

2. The flame-retardant filling material for fireproof door cores according to claim 1, characterized in that, In step C4, the pressure is applied at 5-8 MPa for 3-5 minutes, then increased to 12-15 MPa and held for 5-10 minutes.

3. A method for preparing a flame-retardant filling material for a fireproof door core according to any one of claims 1 to 2, characterized in that, Includes the following steps: S1. Mix 100-150 parts of tetraethyl orthosilicate with 150-200 parts of anhydrous ethanol until homogeneous, add 200-300 parts of deionized water, add hydrochloric acid dropwise to adjust the pH to 2-3, stir at 50-60℃ for 1-1.5 h to form silica sol. S2. Add ammonia to the silica sol to adjust the pH to 8-9, let it stand at room temperature for 12-24 h to form a wet gel, immerse it in a mixture of 8-12 parts of trimethylchlorosilane and 50-80 parts of anhydrous ethanol, keep it at 60-80℃ for 2-3 h, dry it in a supercritical drying device to obtain aerogel powder, add 50-80 parts of anhydrous ethanol, stir for 10-30 min to obtain aerogel slurry; S3. Apply the aerogel slurry evenly to both sides of the compressed fireproof layer, let it stand at room temperature for 10~30 min, place it in a mold after coating, apply pressure of 3~5 MPa, heat to 120~130℃, keep it at that temperature for 2~3 h, let it cool naturally to room temperature, and trim the edge burrs to obtain the flame-retardant filler material.

4. The method for preparing a flame-retardant filling material for a fireproof door core according to claim 3, characterized in that, In step S2, the supercritical drying equipment uses CO2 as the medium and dries the product at 30~35℃ and 7~7.5 MPa for 4~6 h.

5. The method for preparing a flame-retardant filling material for a fireproof door core according to claim 3, characterized in that, In step S3, the aerogel slurry coating method is as follows: place the compressed fireproof layer horizontally on the coating workbench, turn on the scraper coating machine, and evenly scrape the aerogel slurry onto the first side of the compressed fireproof layer with a thickness of 3~5 mm. Let it stand for 8~15 minutes, turn the compressed fireproof layer over, and repeat the scraping steps to complete the coating of the second side of the aerogel slurry.

Citation Information

Patent Citations

  • Preparation method of fireproof and flame-retardant density board

    CN109278151A

  • Wood and bamboo fire retardant and preparation method thereof

    CN114407152A